Case Report: Biallelic variants in MRPS36, encoding a component of the 2-oxoglutarate dehydrogenase complex, cause leigh syndrome - Jiang, Huafang; Xu, Chaolong; Liu, Zhimei; Duan, Ruoyu; Yao, Xingfeng; Fu, Xiaona; Xu, Jiatong; Kang, Xuejing; Yu, Tenghui; Wang, Yuanyuan; Fang, Fang (Frontiers in Pediatrics, 2025)
BackgroundThe MRPS36 gene encodes the E4 subunit of the 2-oxoglutarate dehydrogenase complex (OGDHC), a critical enzyme in the tricarboxylic acid cycle. OGDHC deficiency can lead to metabolic disorders with a clinical spectrum ranging from fatal neonatal lactic acidosis to variable degrees of global developmental delay and movement disorders. To date, a homozygous MRPS36 variant has been reported as a novel cause of Leigh syndrome in only two siblings, who presented with developmental delay, movement disorders, bilateral striatal necrosis, and reduced OGDHC activity.Case presentationWe report a third case of Leigh syndrome associated with MRPS36 variants in a 2-year-old boy. The patient exhibited with global developmental delay, dystonia, early-onset chorea, and elevated serum lactate levels. Follow-up brain magnetic resonance imaging at 2 years revealed progressive degenerative lesions in the bilateral basal ganglia. Muscle biopsy showed abnormal mitochondrial accumulation beneath the sarcolemma, and the oxygen consumption rate was reduced in skin fibroblasts. Whole-exome sequencing identified two novel compound heterozygous MRPS36 variants: c.42+1G>A (p.?) and c.296G>C (p.Arg99Pro).ConclusionThis case supports MRPS36 as a novel pathogenic cause of Leigh syndrome, further expanding the genetic spectrum of the disorder. Key clinical features include developmental delay, involuntary movement disorders, progressive basal ganglia atrophy, and a slowly progressive disease course.